Anatomy of fruit and perianth in Peruvian species of the genus Astrocaryum (Arecaceae): Description and taxonomical importance - Vegas, Cecilia (2008)
The anatomy of fruit and perianth is described for 12 Peruvian species of the genus Astrocaryum. The fruit displays three well-defined layers: exocarp with fiber boundles and sclereids, free or grouped; mesocarp with parenchyma and schizogenous cavities; and heavily sclerified endocarp. Density of vascular bundles of the calyx is higher in the two species of subgenus Astrocaryum and lower in the ten species of subgenus Monogynanthus. Several structures exhibit useful characters for distinguishing subsections and species in the Huicungo section. Such characters include the form and location of fiber packages of the calyx, density of brachysclereids in the distal zone of the exocarp, form of vascular bundles of the corolla, raphides in the mesocarp, presence or absence of trichomes, structure of trichomes, presence or absence of laminar colenchyma in the exocarp, staminodial ring free or adnate and continuity with the corolla. An identification key based on these anatomical characters is supplied.